2006
DOI: 10.1038/sj.mp.4001791
|View full text |Cite
|
Sign up to set email alerts
|

Neural stem cell proliferation is decreased in schizophrenia, but not in depression

Abstract: The phenomenon of adult neurogenesis (AN), that is, the generation of functional neurons from neural stem cells in the dentate gyrus of the hippocampus, has attracted remarkable attention, especially as it was shown that this process is also active in the human brain. Based on animal studies, it has been suggested that reduced AN is implicated in the etiopathology of psychiatric disorders, and that stimulation of AN contributes to the mechanism of action of antidepressant therapies. As data from human post-mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
399
6
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 568 publications
(444 citation statements)
references
References 48 publications
31
399
6
8
Order By: Relevance
“…LIS1, DISC1 and nuclear distribution protein nudE-like 1 (NDEL1) have been shown to be part of a molecular interaction complex relevant in neurodevelopment [55][56][57][58] . Morphological changes in DISC1 mice have been observed including reduced prefrontal cortex volume and impaired growth and dendritic orientation in the dentate gyrus, correlating with findings in human schizophrenia studies [59][60][61] .…”
Section: Disc1supporting
confidence: 59%
“…LIS1, DISC1 and nuclear distribution protein nudE-like 1 (NDEL1) have been shown to be part of a molecular interaction complex relevant in neurodevelopment [55][56][57][58] . Morphological changes in DISC1 mice have been observed including reduced prefrontal cortex volume and impaired growth and dendritic orientation in the dentate gyrus, correlating with findings in human schizophrenia studies [59][60][61] .…”
Section: Disc1supporting
confidence: 59%
“…Clearly, the most direct approach to test this theory is the examination of dentate neurogenesis in depressed patients. So far, there is only one study published recently by Reif et al (2006), which compared the level of neural stem cell proliferation in post mortem hippocampal samples from patients with major depression, bipolar affective disorder and schizophrenia. The authors did not find any evidence of suppressed neurogenesis in the dentate gyri of depressed patients.…”
Section: Stress-induced Structural Changes and Their Potential Implicmentioning
confidence: 99%
“…A clinical study which used post-mortem brain sections of major depressive patients showed no significant difference in the number of hippocampal proliferating cells between normal controls and depressive patients [26]. However, due to experimental limitation in using human tissues, several aspects should be noted.…”
Section: Neurogenesis and Depressive Disordermentioning
confidence: 96%
“…According to a post-mortem study conducted by Reif et al [26], the density of Ki-67 (a nuclear antigen expressed by proliferative cells) in the dentate gyrus of schizophrenia patients was 60% lower than that of control subjects. Surprisingly samples from bipolar disorder and major depression patients did not show a significant lower cell density than the controls.…”
Section: Neurogenesis and Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation